Rights and Protection of Labor of Handloom Towel Factory at Janti, Polanharjo, Klaten - Umrotun Umrotun (Forum Geografi, 1998)
This research is carried out in Janti, Polanharjo, Klaten, Central Java. Most of the female population of this area work as employees in manual industry of towel. The existence of the manual industry of towel enables the female labor force living in the area to have an opportunity to be employees at the industry, as indicated in the population structure that most of the population work as employees of the industry. The aim of this reasearch is to know the characteristic of the population in acordance with age, education, working hours, and experiences. Another aim is to know wage or income, expense of income, employees rights, and the other factors. The method used in this research is survey method with the number of a given sample, where as the data analysis used frequency and cross table. The result of the research indicates that most of the respondents are 20 – 25 years of age. The educational level of the respondents at the average of 40 hours a week, they have worked effectively for 7 – 9 years. The reason is in part they want to meet their daily needs and the other part they consider their jobs are easy to do and accept. The average of their incomes ranges from Rp 20.000 – Rp 50.000 a week. The factors influencing the different of income depend on the seniority and the amount of orking hours. Most of their incomes are spent on primary needs. Their right includes getting a meal once a day and working social insurance, but they don’t get health insurance.